A critical approach on pharmacokinetics, pharmacodynamics, dose optimisation and withdrawal times of oxytetracycline in aquaculture. (26th December 2013) - Rigos, George; Smith, Peter
Abstract Oxytetracycline (OTC) is one of the antibacterial agents that is most commonly used to control bacterial infections in the aquaculture industry worldwide. Thorough knowledge and integration of appropriate drug pharmacokinetics (PK) and pharmacodynamics (PD) in therapeutic schedules are crucial in terms of treatment efficacy and cost, environmental welfare and potentially to human safety. This review provides a much needed critique of published OTC PK and a discussion on OTC PD, dose optimisation and importance of withdrawal times (WT). Overall, the pertinent literature reveals that most published OTC PK information is specific to farmed fish species. Significant variability in experimental design between PK studies rendered interspecies comparisons an almost impossible task. Published PK parameters exert variable relevance to practical application, and moreover, limited or nonexistent information is available for some relevant PK parameters. It is also demonstrated that there is a serious shortage of data simultaneously relating dose regimen, PK, PD data and clinical outcomes. This results in difficulties in applying available PK data to the improvement in current dose regimen. Efficacy studies and PK/PD data currently available do not allow improvements in the interpretive criteria used by laboratories; thus, for the present, clinical evaluations must rely on wild‐type epidemiological cut‐off values (COWT). Regarding OTC removal, the WT estimates that have been made for farmed crustaceans are much shorter than those for finfish. However, this fact does not necessarily ensure that these products are unlikely to result in contravention of regulatory limits.